Examining the kinetics of the thermal polymerization of commercial aromatic bis‐benzoxazines. Issue 14 (14th May 2014) - Hamerton, Ian; McNamara, Lisa T.; Howlin, Brendan J.; Smith, Paul A.; Cross, Paul; Ward, Steven
ABSTRACT Three commercial bis‐benzoxazine monomers based on the aniline derivatives of bisphenol A (BA‐a), bisphenol F (BF‐a), and 3, 3′‐thiodiphenol (BT‐a) are examined using a variety of spectroscopic, chromatographic, and thermomechanical techniques. The kinetics of the polymerization of BA‐a were found to be well described using an autocatalytic model for which values of n = 1.39 and m = 2.49 were obtained for the early and later stages of reaction respectively (activation energy = 81–88 kJ/mol.). Following recrystallization the same monomer yielded values of n = 1.80, m = 0.92, and Ea = 94–97 kJ/mol. BF‐a and BT‐a were also found to be well described using an autocatalytic model for which values of n = m = 2.11 (BF‐a) and n = 2.10, m = 1.47 (BT‐a) were obtained for the early and later stages of reaction (activation energy = 80–84 kJ/mol. for BF‐a and 88–95 kJ/mol. for BT‐a). The kinetic data are compared with parallel studies involving chemically initiated benzoxazine monomers. Molecular simulation is used to examine the rotational freedom of the central bridging units and this is related to the degree of conversion achieved. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 2068–2081